Mastitis in goat: A review of etiology, epidemiology, economic impact, and public health concerns - Abebe Tibebu; Yechale Teshome; Habtamu Tamrat; Adane Bahiru (One Health)
Mastitis is a multifactorial disease of mammals that has substantial implications on production, welfare, and public health, but it is far less studied in goats. This study reviewed the causes, diagnostic tests, economic and public health impacts, and prevalence of mastitis in goats. The review revealed that mastitis in goats could be clinical (CM) or subclinical (SCM). Bacteria, such as Staphylococcus, Streptococcus, E. coli, and Mycoplasma, are the main cause of mastitis in goats. Mastitis in goats is influenced by intrinsic factors like breed, parity, age, and lactation stage, and extrinsic factors like pathogens, environment, and management. Somatic cell count and the California mastitis test are common diagnostic tests for SCM, but their reliability is questionable due to the broader range of somatic cells in goat milk. Dry period therapy and early interventions are the best options for mastitis treatment and control methods, while temporal milking stops can enhance immunity. Mastitis can affect animal welfare, milk yield, quality, marketability, and public health due to disease transmission and intoxication. The pooled prevalence of mastitis was found to be 36 % (95 % CI: 25–50). The prevalence of CM was often less than 5 % and occurred sporadically. In contrast, SCM was the most prevalent form (prevalence ranges from 30 % to 50 %). In conclusion, despite goats being the foundation of financial stability and food security in rural households, and with an estimated prevalence comparable to cows, mastitis research is frequently overlooked. Given goats' importance in rural households' economies, there is a need to shift research priorities and strengthen multidisciplinary collaborations to address zoonotic diseases associated with mastitis, at the intersection of animal, environmental, and human health.